Visible‐Light‐Induced Hydrogen Generation from Mixtures of Hydrogen Boride Nanosheets and Phenanthroline Molecules - Jumpei Takeshita; Hayato Tsurugi; Andi Mauliana; Akira Yamaguchi; Takahiro Kondo; Masahiro Miyauchi (Advanced Science)
Abstract Hydrogen boride (HB) nanosheets are recognized as a safe and lightweight hydrogen carrier, yet their hydrogen (H2) generation technique has been limited. In the present study, nitrogen‐containing organic heterocycles are mixed with HB nanosheets in acetonitrile solution for visible‐light‐driven H2 generation. After exploring various nitrogen‐containing heterocycles, the mixture of 1,10‐phenanthroline molecules (Phens) and HB nanosheets exhibited significant H2 generation even under visible light irradiation. The quantum efficiency for H2 generation of the mixture of HB nanosheets and Phens is 0.6%. Based on spectroscopic and electrochemical analyses and density functional theory (DFT) calculations, it is determined that radical species generated from Phens with electrons and protons donated by HB nanosheets are responsive to visible light for H2 generation. The HB nanosheets/Phens mixture presented in this study can generate H2 using renewable energy sources such as sunlight without the need for complex electrochemical systems or heating mechanisms and is expected to serve as a lightweight hydrogen storage/release system.